Circulating Soluble Suppression of Tumorigenicity 2 Predicts Recurrence After Radiofrequency Ablation of Persistent Atrial Fibrillation - Tan, Ruopeng; Yu, Haixu; Han, Xu; Liu, Yang; Yang, Xiaolei; Xia, Yun-Long; Yin, Xiaomeng (Frontiers in Cardiovascular Medicine, 2021)
ABSTRACT Objective: A more extensively fibrotic left atrium contributes to atrial fibrillation (AF) occurrence, persistence and recurrence. The soluble suppression of tumorigenicity 2 (sST2) has emerged as a ventricular fibrotic biomarker for patients with heart failure. The present study is to investigate associations between circulating sST2 and risk of recurrence after ablation in AF patients. Methods: We measured the baseline plasma level of sST2 from patients with persistent AF (n=117) and paroxysmal AF (n=93) patients. Patients were followed up for 15 month after ablation. The relationship between circulating sST2 and recurrence was assessed by multivariable Cox regression. The cutoff value of sST2 was determined by receiver operating characteristic curve. The relationship between baseline sST2 level and left atrial volume index (LAVI) was assessed by multivariate linear regression analysis. Serial sST2 measurements were also conducted after 24 h, 6 months and 15 months of ablation. ST2 localization was examined in left atrial appendages of persistent AF patients by immunohistochemistry and western blot. Results: Baseline sST2 positively associated with LAVI in the persistent AF group, and elevated sST2 (≥39.25 ng/ml) independent increased the risk of recurrence after ablation (area under the curve=0.748), with hazard ratio of 1.038 (95% confidence interval 1.017-1.060, P<0.001) when adjusted for co-variables. In contrast, elevated sST2 can not predict recurrence in paroxysmal AF. Conclusions: In persistent AF patients, increased sST2 serves as a marker of recurrence after radiofrequency ablation. Patients with sST2≥39.25 ng/ml are more likely to develop recurrence within a year.